Impact of high-k insulators on electrical properties of junctionless double gate strained transistor - Kaharudin K.E.; Salehuddin F.; Zain A.S.M.; Jalaludin N.A.; Arith F.; Junos S.A.M.; Ahmad I. (Institute of Advanced Engineering and Science, 2025)
High-k dielectric insulators are required to reduce leakage and increase transistor performance. They are able to impact the mobility of carriers in transistors positively, leading to better device performance in advanced transistor architecture. Nevertheless, an in-depth analysis of how high-k dielectric insulators influence transistor characteristics must be carried out to determine their suitability. The objective of this study is to investigate the impact of high-k insulators towards electrical properties of junctionless double gate strained transistor. The simulation works is done using process/device simulator Silvaco Athena/Atlas. Based on the retrieved results, the magnitude of ION, on-off ratio, gm, and Cint for TiO2-based device are approximately 63%, 99%, 62%, and 89% respectively higher than the lowest permittivity material-based device. The TiO2-based device also exhibits the lowest magnitude in IOFF and SS compared to others. However, a significant degradation in fT magnitude have been observed for TiO2-based device significantly due to its large capacitances. ? 2024 Institute of Advanced Engineering and Science. All rights reserved.